2000
DOI: 10.1007/s004420050969
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal versus biochemical limitations to dynamic photosynthetic performance in four tropical rainforest shrub species

Abstract: Photosynthetic performance under dynamic light regimes was assessed in four different species of tropical shrubs from the family Rubiaceae via field gas exchange measurements conducted on Barro Colorado Island, Panamá. Rates of photosynthetic induction and induction loss were assessed throughout the day in both the wet and dry seasons in order to determine the relative roles of stomata and biochemistry in limiting photosynthetic performance under transient light conditions. A high degree of coordination was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
6
53
1
Order By: Relevance
“…6) -by contrast to results reported for many other species (Pepin & Livingston, 1997;Allen & Pearcy, 2000a;Naumberg & Ellsworth, 2000). Large variation in stomatal response times have, however, been reported (Allen & Pearcy, 2000a;Naumberg & Ellsworth, 2000) Estimated daily C gain was calculated assuming a clear spring day using irradiance curves from 20 October (as in Fig. 1) from four positions at both canopy levels and steady-state photosynthesis characteristics (eqn 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6) -by contrast to results reported for many other species (Pepin & Livingston, 1997;Allen & Pearcy, 2000a;Naumberg & Ellsworth, 2000). Large variation in stomatal response times have, however, been reported (Allen & Pearcy, 2000a;Naumberg & Ellsworth, 2000) Estimated daily C gain was calculated assuming a clear spring day using irradiance curves from 20 October (as in Fig. 1) from four positions at both canopy levels and steady-state photosynthesis characteristics (eqn 1).…”
Section: Discussionmentioning
confidence: 96%
“…In a tropical ecosystem, stomatal response times determined the photosynthetic response times to sunflecks when water was limiting, but stomata exhibited little or no control when water was not limiting (Allen & Pearcy, 2000a). In a temperate pine plantation, stomatal responses generally limited sunfleck responses, but to different extents in different species (Naumberg & Ellsworth, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of photosynthetic induction have played an important role in elucidating the mechanisms of photosynthesis, and in the development of dynamic models (Walker, 1973;Govindjee, 1995;. It is now generally accepted that induction of photosynthesis (at the scale of minutes) is, at least, limited by activation of Rubisco and opening of the stomata (Allen and Pearcy, 2000a;Vialet-Chabrand et al, 2016). Other potential effects may be associated with activation of other enzymes in the Calvin cycle (Sassenrath-Cole et al, 1994), build-up of metabolites in the Calvin cycle (Walker, 1973), and activation of sucrose phosphate synthase (Stitt and Grosse, 1988).…”
Section: Photosynthesis In Its Natural Environmentmentioning
confidence: 99%
“…Furthermore, several authors have reported that non-uniform stomata opening (i.e. stomata patchiness) in response to a sudden increase in irradiance might cause differences in biochemical activation throughout the leaf (KIRSCHBAUM & PEARCY, 1988b; TINOCO-OJANGUREN & PEARCY, 1993a;KÜPPERS et al, 1999;ALLEN & PEARCY, 2000).In order to grow in low irradiance environments such as the forest understorey, where plants have low carbon gain (CHAZDON et al, 1996; STRAUSS-DEBENEDETTI & BAZZAZ, 1996), plants must minimize carbon loss trough reduction of both respiration and tissue construction costs (GIVNISH, 1988), attaining 101 a positive leaf carbon balance. Our data are in accordance with those previously reported since all species studied showed significant higher R D in the forest gap than in the understorey (Figures 2, 4).…”
mentioning
confidence: 99%
“…Furthermore, several authors have reported that non-uniform stomata opening (i.e. stomata patchiness) in response to a sudden increase in irradiance might cause differences in biochemical activation throughout the leaf (KIRSCHBAUM & PEARCY, 1988b; TINOCO-OJANGUREN & PEARCY, 1993a;KÜPPERS et al, 1999;ALLEN & PEARCY, 2000).…”
mentioning
confidence: 99%